The Human Rights and The Human Dignity in The Contemporary Bioethics - Bołoz, Wojciech (Studia Ecologiae et Bioethicae, 2004)
In contemporary bioethics dominate two trends dealing with two basic ethical solutions. First of them is utilitarianism concerning utility as a criterion of judging between what is right and what is wrong. The second trend applies to human rights and human dignity, which are to be obeyed without any exceptions. Utilitarianism protects the strong and prosperous people in society and excludes those who are weak and not capable of independent life. The concept of human dignity protects each and every human being including the weakest ones. It is therefore characterized by real humanitarianism. In addition, it has one more outstanding virtue; in the contemporary world, it is the most widespread and understandable ethical code. It enables people of different civilizations to communicate with understandable ethical language. In the world constantly undergoing global processes, it is of great value. Although there are a number of discussions concerning the way of understanding human dignity and human rights, their universal and ethical meaning; there are certain international acts of law concerning biomedicine that support the concept of human dignity as the most adequate concept for contemporary bioethics. As an example, the European Convention on Bioethics can be taken. The article includes the most significant topics concerning understanding, history, and application of law and human dignity in bioethics.